2015
DOI: 10.1002/cncr.29522
|View full text |Cite
|
Sign up to set email alerts
|

Novel targeted agents for the treatment of lung cancer in China

Abstract: Since the discovery of epidermal growth factor receptor mutations and epidermal growth factor receptor tyrosine kinase inhibitors, lung cancer treatment in China has entered the precision era. However, novel targeted agents based on novel biomarkers still need to be developed. In the current study, the authors review the biomarker features of lung cancer in the Chinese population and the novel agents that are aimed at novel targets. Furthermore, they discuss issues that require improvement for the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In this NGS‐based study of Chinese patients with NSCLC, a comprehensive profile of genomic alterations was constructed. In gene mutations of EGFR , KRAS , and ALK , Chinese patients with NSCLC were different from the Western population, as the former had a much higher frequency (47.6% vs. 20.0%) of EGFR mutations and ALK rearrangements (7.8% vs. 4.1%) but a significantly lower frequency (10.8% vs. 32.0%) of KRAS mutation than the latter , which was consistent with previous reports . Nearly three quarters of Chinese patients with NSCLC harbored at least one druggable genomic alteration of driver genes recommended by the NCCN guideline, revealing the different clinical characteristics of Chinese patients.…”
Section: Discussionsupporting
confidence: 87%
“…In this NGS‐based study of Chinese patients with NSCLC, a comprehensive profile of genomic alterations was constructed. In gene mutations of EGFR , KRAS , and ALK , Chinese patients with NSCLC were different from the Western population, as the former had a much higher frequency (47.6% vs. 20.0%) of EGFR mutations and ALK rearrangements (7.8% vs. 4.1%) but a significantly lower frequency (10.8% vs. 32.0%) of KRAS mutation than the latter , which was consistent with previous reports . Nearly three quarters of Chinese patients with NSCLC harbored at least one druggable genomic alteration of driver genes recommended by the NCCN guideline, revealing the different clinical characteristics of Chinese patients.…”
Section: Discussionsupporting
confidence: 87%
“…The efficacy results are consistent with prior reports with EGFR inhibitors in this patient population, although relatively little information has been provided regarding the dose delivery, duration of therapy, and dose reductions from toxicity. Of concern, 3 patients in the study by Ni et al developed pulmonary toxicity, including a grade 5 event . Notably, in this phase 3 study of icotinib versus gefitinib, no cases of pulmonary toxicity were observed.…”
mentioning
confidence: 66%
“…Of concern, 3 patients in the study by Ni et al developed pulmonary toxicity, including a grade 5 event. 5 Notably, in this phase 3 study of icotinib versus gefitinib, no cases of pulmonary toxicity were observed. The higher predilection of Asian patients to develop pulmonary toxicity with EGFR tyrosine kinase inhibitors has been reported previously.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Significant efforts by the Chinese government during the last 2 years have led to improvements in the overall clinical research environment [14]. Now the CFDA is actively reforming the regulatory framework for the approval of novel agents, which has introduced a “four-color light” strategy and will likely further adjust its policies to reflect advances in large international clinical trials of immunotherapy [15].…”
Section: Domestic Clinical Trialsmentioning
confidence: 99%